Analisis Problematika Lelang Sebagai Eksekusi Putusan Pengadilan dalam Perkara Perdata - Rifki Firzatullah, Muhammad; Ilmar Irawan, Bian; Akmal Rohmatino, Hasan; Jajuly, Rijal; Munawar, Fiqri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This article discusses various issues that arise in the implementation of execution auctions, including the obstacles faced by the parties involved. This research analyzes the factors causing delays or failures in the execution auction process, including legal and administrative constraints that often occur. The research findings indicate that some main obstacles include reoccupation of auctioned objects, resistance from the losing party in the case, and a lack of coordination among law enforcement agencies, the judiciary, and related parties. This research is highly relevant to improving the civil execution system and provides valuable insights for legal practitioners, law enforcement agencies, and researchers interested in civil. This research also provides solutions and recommendations to enhance the efficiency and effectiveness of execution auctions in civil cases.